ANALISIS KESESUAIAN PENDIDIKAN GURU DENGAN MATA PELAJARAN PADA SEKOLAH MENENGAH DI KABUPATEN BULUKUMBA - Halimatuzzahrah; Nur Hikma; Fahira; Mirnawati; Elfiana Handerson; Haeril Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the suitability between teachers’ educational backgrounds and the subjects they teach in senior high schools, vocational high schools, and Islamic senior high schools in Bulukumba Regency. The study was motivated by the existence of mismatches between teachers’ academic qualifications and the subjects taught, which may affect the quality of learning. This research used a qualitative descriptive approach. The subjects of the study consisted of teachers and school principals or vice principals selected through purposive sampling techniques. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that most teachers had taught in accordance with their educational backgrounds. This suitability positively affected teachers’ mastery of learning materials, teaching strategies, confidence in teaching, and effectiveness of the learning process. However, there were still several teachers teaching outside their fields of expertise due to limited teaching staff and school needs. To overcome this issue, schools and teachers carried out competency development through training, workshops, MGMP activities, and the Teacher Professional Education Program (PPG). Therefore, the suitability between teachers’ educational backgrounds and the subjects taught plays an important role in improving the quality of education and learning effectiveness in schools.